Case report: vitamin D‐dependent rickets type 1 caused by a novel CYP27B1 mutation. Issue 12 (5th November 2015) - Füchtbauer, Laila; Brusgaard, Klaus; Ledaal, Pål; Frost, Morten; Frederiksen, Anja L.
Key Clinical Message: Vitamin D‐dependent rickets type 1 VDDR‐1 is a recessive inherited disorder with impaired activation of vitamin D, caused by mutations in CYP27B1 . We present long‐time follow‐up of a case with a novel mutation including high‐resolution peripheral quantitative computed tomography of the bone. Adequate treatment resulted in a normalized phenotype. Abstract : Vitamin D‐dependent rickets type 1 VDDR‐1 is a recessive inherited disorder with impaired activation of vitamin D, caused by mutations in CYP27B1 . We present long‐time follow‐up of a case with a novel mutation including high‐resolution peripheral quantitative computed tomography of the bone. Adequate treatment resulted in a normalized phenotype.